Pelestarian Tari Sinok dalam Event Pasar Ndoro Bei Demak - Jayidul Amri, Muhammad; Miftah M. Nur, Dany (Institut Agama Islam Negeri Ponorogo, 2025)
Sinok dance is a dance creation initiated by Mrs. Ika Febriani Laksaningtyas around 2016, precisely after the establishment of Padma Baswara Demak Dance Studio. She initiated this dance as a form to illustrate cultural acculturation between China and Java. The revitalization of Sinok Dance is based on the need for a typical Demak art form to be performed at festivals, one of which is the Ndoro Bei Demak market event. The following note will explore more deeply the meaning and cultural values in the Sinok Dance procession at the Ndoro Bei market event in Demak, the dynamics in Sinok Dance, and the challenges faced by dancers in Sinok Dance. This study aims to analyze the meaning of movement, the dynamics of presentation, and the challenges of regeneration in the performance of Sinok Dance as part of the preservation of local culture. The research methods used by researchers are field studies, observations, and interviews. The results of this study explain that first, the meaning of Sinok Dance movements, namely: small running movements, jumping movements, and movements playing broom sticks. Then, the cultural values in Sinok Dance are: social value, aesthetic value, and educational value. Second, the dynamics that occur in Sinok Dance are: the dynamics of dancers' costumes, the dynamics of the number of dancers, and the dynamics of the tools used by dancers. Third, the challenges faced by dancers in the Sinok Dance procession are: the lack of regeneration of young male dancers, the lack of regeneration of Sinok Dance teachers, and the lack of consistent Sinok Dance training. This research is expected to contribute to the preservation of local arts and culture and encourage the strengthening of the cultural identity of the Demak community through the development of regional dance creations.